Implementing Regional Regulation No. 1/2014: Rehabilitative Social Work Practices for Homelessness in Yogyakarta - Setyowati, Yuli; Tentyarini, Dita; Bumi, Niemas Hanatha (TheJournalish: Social and Government, 2025)
This study examines the implementation of social welfare services for beggars and homeless individuals in Yogyakarta, Indonesia, based on Regional Regulation No. 1 of 2014. Using a qualitative case study approach, data were collected through in-depth interviews with clients and government staff at the Social Service Agency (Dinas Sosial), as well as document analysis and direct observation. Guided by Ife and Tesoriero’s community development framework, the analysis identifies four key roles: facilitator, educator, representative, and technical. The results show that the facilitation role is evident in the initial assessment and participatory engagement with clients, while the technical role involves accurate data collection and professional referrals. The educator role appears in public awareness campaigns and in-house client coaching, while the representative role reflects advocacy and coordination with other agencies. The findings highlight challenges such as limited rehabilitation facilities, low community participation, and a short intervention timeframe. These findings underscore the importance of holistic and ethical approaches in social services for vulnerable populations. The study concludes that while the implementation aligns with the regulation’s rehabilitative mandate, enhancements in infrastructure, community engagement, and policy support are needed for more sustainable and inclusive outcomes.